Assessment of Alumni’s Professional Preparedness and Workforce Integration of Mechanical Engineering Departement State University of Surabaya - Novita Sari, Handini; Vinaya Wijanarko, Diastian; Iskandar, Iskandar; Effendy, Mohammad; Juwantono, Heri (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Alumni professional readiness and success in the workplace are critical indicators of a university’s educational quality and reputation. Method: The method used in this research is quantitative, The object of this study was alumni of the Mechanical Engineering Undergraduate Study Program, class of 2023, classes 106, 107, 108, and 109 with a total of 73 respondents, where data information about alumni will be acquired using the study tracer application. Results:The research results show that the competencies mastered by alumni are quite good, with the highest competency mastery in teamwork and ethics. In contrast, the competency that alumni need to improve is communication. 66.67% of alumni work in the private sector, 11.76% work in BUMN/BUMD, 5.88% choose to be self-employed/own companies, 9.80% work in government agencies, and 5.88%, with a period of obtaining employment in the first 6 months after graduating reached 90.38%. Novelty: This study’s strategy, which links the abilities acquired during the study period with alumni’s post-graduation job accomplishments and analyzes their preparedness for obstacles in the workplace, is what makes it novel. It will summarize the skills and competencies employers seek in today’s workforce and offer fresh perspectives on how higher education courses might be better tailored to industry demands.